Applications Of Science And Technology In Malaysian Cosmetic Industry - Md Kasim , Raihani; Nordin, Mohd Ridzuan (2006)
The use of cosmetics and toiletries is an integral component of life. Malaysian cosmetics and toiletries market recorded approximately RM 3 billion sales in 2004. Facial care contributed 60% of the market value in the skin care segment. In the facial care segment, moisturiser is identified as the most marketable product. Moisturiser is used to restore the barrier function of the epidermis; provide a soothing protective film ; increasing water content of the skin and other properties such as anti-ageing. The function is depending on the ingredient used in the formulation of the product. Although there is a strict regulation on cosmetics product, the development of ingredient technology is continuously evolving to cater the sophisticated consumer demand. Application of science and technology is critical to ensure the cosmetic industry to remain competitive and sustainable. The future of Malaysian skin care industry is hence dependent on the application of science and technology to success. A study on the local entrepreneurs regarding the formulation technology and marketing of facial moisturiser is recommended.